Alterations in Fetal Doppler Parameters Before and Twenty-Four Hours After Radiofrequency Ablation for Twin Reversed Arterial Perfusion Sequence - Zhang, Lan; Liu, Hongli; Huang, Shuai; Tong, Chao; Wang, Zhigang; Qi, Hongbo; Baker, Philip N.; Kilby, Mark D. (Frontiers in Medicine, 2022)
Objective: To evaluate alterations in the fetal Doppler parameters of pump fetuses before and 24 h after radiofrequency ablation surgery for twin reversed arterial perfusion sequence (TRAPs). Methods: This is a retrospective study of 28 pump fetuses in TRAPs and 28 normal control twins between 2016 and 2021. The fetal Doppler parameters, including the umbilical artery pulsatility index (UA-PI), middle cerebral artery peak systolic velocity (MCA-PSV), middle cerebral artery pulsatility index (MCA-PI) and cerebroplacental ratio (CPR), of the controls and pump fetuses before and 24 h after surgery were compared. Results: An increasing trend and a further increase in the MCA-PSV, MCA-PI, MCA-PSV Z score, and MCA-PI Z score after surgery were observed in pump fetuses with a gestational age (GA) ≥ 20 weeks; however, such changes were not observed in those with a GA < 20 weeks. The UA-PI and CPR before and after surgery were not different between control and pump fetuses, whether the GA was ≥ 20 or < 20 weeks. Conclusion: In the middle second trimester, the pump fetus might suffer from high cardiac output rather than hypoxemia before surgery and congestive heart failure or hemodilutional anemia after surgery. This may provide some theoretical evidence in favor of early intervention, rather than waiting until a more advanced GA, to avoid unnecessary hemodynamic alterations.